2015
DOI: 10.1007/s11096-015-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of theory in research

Abstract: All researchers should consider the theoretical basis for their studies very early on in the planning stage. The aim of this paper is to describe and discuss how theory (a 'comprehensive explanation of some aspect of nature that is supported by a body of evidence') can inform and improve the quality and relevance of pharmacy-based research. Theories can be applied at many stages of quantitative and qualitative (and mixed) research processes, including: providing rationale for the study; defining the aim and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 17 publications
2
58
0
Order By: Relevance
“…The study reported here aimed to explore older people's adherence behaviour using the theoretical domains framework (TDF) as the underpinning model of theoretical determinants of behaviour. The TDF acts as a theoretical lens through which key determinants (ie theoretical domains) of the target behaviour (ie medication adherence) can be identified for targeting with a behaviour change intervention . Key theoretical domains can then be mapped to appropriate behaviour change techniques (BCTs) .…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here aimed to explore older people's adherence behaviour using the theoretical domains framework (TDF) as the underpinning model of theoretical determinants of behaviour. The TDF acts as a theoretical lens through which key determinants (ie theoretical domains) of the target behaviour (ie medication adherence) can be identified for targeting with a behaviour change intervention . Key theoretical domains can then be mapped to appropriate behaviour change techniques (BCTs) .…”
Section: Introductionmentioning
confidence: 99%
“…For this study to constitute credibility, trustworthy, dependability, conformability, transferability initiatives like taking data from different layers of work force, members check, data display, detail presentation of data in rich description, maintain audit trail and compare congruity with other studies are taken (Merriam, 2002;Morrow, 2005;Miles, Huberman, & Saldaña, 2014). Moreover, in linking the pieces of findings with exiting knowledge, the open system theory is applied as theoretical lens (Stewart & Klein, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…20 NPT is a sociological tool, consisting of 4domains, that has been used to evaluate implementation processes in a broad range of complex health care practices. [22][23][24] Combined, Kotter and NPT provide rigorous support to explore the chosen processes.…”
Section: Design and Underlying Theoriesmentioning
confidence: 99%